Distribution pattern of Algal species in Shahpura Lake, Bhopal, with respect to physicochemical parameters. - Shukla, Sangeeta (International Journal of Pharmaceutical & Biological Archive, 2017)
Shahpura Lake is situated in the posh area of Bhopal city. It is a man –made perennial lake, constructedduring 1974-75.Lake water is extensively used for recreational and fishing activity. Lake is surroundedby human habitation and receives untreated domestic sewage from various points. A regular monitoringin physico-chemical parameters and distributional pattern of algal species was conducted during rainyand winter season(2016).The study reveals physico-chemicals parameters and their relation to the growthand distribution of algal population .About 29 algal species was recorded, out of which 12 algal specieswas found to be dominant during study period.